2018
DOI: 10.1155/2018/5404093
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in Keratinocytes and Langerhans Cells: Relevance to the Epidermal Homeostasis

Abstract: In the skin, the epidermis is continuously exposed to various kinds of external substances and stimuli. Therefore, epidermal barriers are crucial for providing protection, safeguarding health, and regulating water balance by maintaining skin homeostasis. Disruption of the epidermal barrier allows external substances and stimuli to invade or stimulate the epidermal cells, leading to the elicitation of skin inflammation. The major components of the epidermal barrier are the stratum corneum (SC) and tight junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 121 publications
0
14
0
1
Order By: Relevance
“…HPV E6 protein also forms Zn 2+ -dependent soluble agglomerates, whereas the metal chelating agent EDTA stabilizes its monomeric form and destabilizes existing agglomerates [ 89 ], and where Cu 2+ complexes also cause E6 aggregation, inhibiting its function [ 222 ]. Recent work has demonstrated that the keratinocyte-derived body’s epidermal barrier is formed by the filaggrin protein [ 223 ], a protein that phase-separates and that has been found to bind Cu 2+ and be regulated by Zn 2+ [ 224 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV E6 protein also forms Zn 2+ -dependent soluble agglomerates, whereas the metal chelating agent EDTA stabilizes its monomeric form and destabilizes existing agglomerates [ 89 ], and where Cu 2+ complexes also cause E6 aggregation, inhibiting its function [ 222 ]. Recent work has demonstrated that the keratinocyte-derived body’s epidermal barrier is formed by the filaggrin protein [ 223 ], a protein that phase-separates and that has been found to bind Cu 2+ and be regulated by Zn 2+ [ 224 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zn 2+ bound to highly conserved ZnFs of influenza virus M1 matrix proteins is described as the determining factor of conformational transition of capsids in acidic environments, leading to their uncoating [ 226 ]. Similar to HIV-1 Gag, M1 is highly disordered, contains both RRMs and ZnFs ( Figure 1 ), and is the most abundant viral protein, responsible for both recruiting newly synthesized RNP cores from the nucleus for encapsidation and for maintaining the virion structure [ 224 ]. Upon infection of cells, the influenza M2 protein opens ion channels to permit flux into virions, and resulting pH flux and Zn 2+ cause virus uncoating by destabilizing Zn 2+ -bound M1 protein [ 226 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lethal acrodermatitis, an autosomal recessive hereditary disease typically seen in Bull Terrier dogs, has been associated with acrodermatitis enteropathica, a rare autosomal recessive disease of humans caused by a mutation of a gene that encodes expression of ZIP4, affecting both intestinal absorption of zinc and Langerhans cells [ 106 ]. Young dogs carrying the disease may exhibit anorexia, poor growth, impaired immune responses, and skin lesions located in the face, head, and paws, compatible with parakeratotic hyperkeratosis [ 107 ], concomitant with low serum zinc [ 108 , 109 ].…”
Section: Role Of Zinc Status In the Occurrence Of Diseasementioning
confidence: 99%
“…Indeed, an imbalance of T-helper (Th1):Th2 cell ratio is associated with zinc deficiency, as its flux and homeostatic zinc signals are crucial for proper T-cell differentiation [124]. This suggests that zinc deficiency contributes to the disruption of skin homeostasis as the Th2-type immune response downregulates the expression of proteins involved in the formation and maintenance of the epidermal barrier (e.g., filaggrin, involucrin) [106]. Olivry et al reported dendritic cell hyperplasia and higher percentages of IgE+ cells in canine atopic dermatitis and increased epidermal Langerhans cell counts in lesional specimens suggesting an epidermal allergen contact that indicates a role of antigen-presenting cells in the pathogenesis of the disease [125].…”
Section: Canine Atopic Dermatitismentioning
confidence: 99%
“…Нестача цього мікроелемента призводить до підвищення проникності, зокрема, рогового шару та щільних сполук. Одним із наслідків такого дисбалансу може бути розвиток атопічного дерматиту [11].…”
Section: участь цинку в реалізації імунної відповідіunclassified